Tribology of reciprocating engines : proceedings of the 9th Leeds-Lyon Symposium on Tribology held in Bodington Hall, the University of Leeds, England, 7-10 September 1982 - Dowson, D.; Taylor, C. M.; Godet, M.; Berthe, D. (Butterworth & Co (Publishers) Limited, 1983)
Tribology of Reciprocating Engines.